ENHANCING NARRATIVE WRITING SKILLS THROUGH ANIMATION VIDEOS IN THE EFL CLASSROOM - Zein Tahwiana; Regina Regina; Eka Fajar Rahmani; Yohanes Gatot Sutapa Yuliana; Wardah Wardah (Getsempena English Education Journal)
This study examined the use of animation videos to teach narrative text writing to SMP Negeri 21 Pontianak eighth-grade students. The study used the 8B class of SMP Negeri 21 Pontianak as the research sample, consisting of 35 students taken from cluster random sampling from a population of 209 students. This pre-experimental study also used a group pre-test and post-test design, consisting of three procedures: pre-test, treatment, and post-test. This study was conducted in two treatments for 120 minutes per meeting by using animation videos to teach narrative text. Two methods were used in the treatment: the first was a full viewing, in which learners watched the entire video without pausing to learn about the plot, characters, and moral lessons. The second method is freeze with text, in which the teacher paused the video and explained each of the generic structures and language features in the narrative text based on the video scenes. The data were gathered through a narrative writing test for the pre-test and post-test, and as for the assessment, a rubric consisting of content, organization, vocabulary, grammar, and mechanics. The finding revealed that animation videos effectively taught students narrative text writing skills. The t-test result was higher than the t-table (10.90>1.691), indicating the effectiveness. The effect size was also categorized as a “very strong effect” with a calculation value of 1.74. These findings imply that animation videos can be used as media support to teach narrative text writing to students, especially those at SMP Negeri 21 Pontianak.